Student Mathematical Communication in Solving Two Variable System of Linear Equations - Fidia Lestariningsih; Tjang Daniel Chandra; Swasono Rahardjo (Jurnal Pendidikan Sains, 2021)
Abstract: Communication is a basic skill for students in mathematics. This study describes students' mathematical communication to solve mathematical problems. The results show that high-cognitive-abilities students are able to consolidate and organize mathematical thinking through the communication of students with moderate and low abilities. All subjects use mathematical language to present mathematical ideas. The high-cognitive student is able to communicate mathematical thinking correctly to friends, teachers, and others. All subjects have not been able to analyze and evaluate other mathematical ideas and strategies.Abstrak: Komunikasi menjadi keterampilan dasar yang diperlukan oleh siswa dalam matematika. Penelitian ini mendeskripsikan kemampuan komunikasi matematis siswa dalam pemecahan masalah matematika. Hasil penelitian bahwa siswa yang mempunyai kemampuan matematika tinggi lebih mampu mengomunikasikan, menguatkan ide dan mengatur pemikiran matematis dibandingkan siswa berkemampuan matematika sedang dan rendah. Semua subjek penelitian bisa memaparkan ide-ide matematisnya dengan menggunakan bahasa matematis. Siswa berkemampuan tinggi mampu mengomunikasikan ide-ide dan gagasan matematisnya dengan tepat kepada guru, teman sebaya dan orang lain. Semua subjek penelitian belum mampu menjabarkan dan menilai gagasan matematis yang dimiliki orang lain.